Feasibility of adjunct therapeutic hypothermia treatment for hyperammonemia and encephalopathy due to urea cycle disorders and organic acidemias - Lichter-Konecki, Uta; Nadkarni, Vinay; Moudgil, Asha; Cook, Noah; Pöschl, Johannes; Meyer, Michael T.; Dimmock, David; Baumgart, Stephen (Molecular genetics and metabolism, 2013)
Background - Children with urea cycle disorders (UCDs) or organic acidemias (OAs) and acute hyperammonemia and encephalopathy are at great risk for neurological injury, developmental delay, intellectual disability, and death. Nutritional support, intravenous alternative pathway therapy, and dialysis are used to treat severe hyperammonemia associated with UCDs and nutritional support and dialysis are used to treat severe hyperammonemia in OAs. Brain protective treatment while therapy is initiated may improve neurological and cognitive function for the lifetime of the child. Animal experiments and small clinical trials in hepatic encephalopathy caused by acute liver failure suggest that therapeutic hypothermia provides neuroprotection in hyperammonemia associated encephalopathy. We report results of an ongoing pilot study that assesses if whole body cooling during rescue treatment of neonates with acute hyperammonemia and encephalopathy is feasible and can be conducted safely. - Methods - Adjunct whole body therapeutic hypothermia was conducted in addition to standard treatment in acutely encephalopathic, hyperammonemic neonates with UCDs and OAs requiring dialysis. Therapeutic hypothermia was initiated using cooling blankets as preparations for dialysis were underway. Similar to standard therapeutic hypothermia treatment for neonatal hypoxic ischemic encephalopathy, patients were maintained at 33.5°C±1°C for 72h, they were then slowly rewarmed by 0.5°C every 3h over 18h. In addition data of age-matched historic controls were collected for comparison. - Results - Seven patients were cooled using the pilot study protocol and data of seven historic controls were reviewed. All seven patients survived the initial rescue and cooling treatment, 6 patients were discharged home 2-4weeks after hospitalization, five of them feeding orally. The main complication observed in a majority of patients was hypotension. - Conclusion - Adjunct therapeutic hypothermia for neonates with UCDs and OAs receiving standard treatment was feasible and could be conducted safely in pediatric and neonatal intensive care units experienced in the application of therapeutic hypothermia in critically ill neonates. However, including adjunct therapeutic hypothermia in the already involved treatment regimen of critically ill patients with hyperammonemia and encephalopathy adds to the complexity of care and should not be done unless it is proven efficacious in a randomized clinical trial.